2000
DOI: 10.1001/archotol.126.7.895
|View full text |Cite
|
Sign up to set email alerts
|

Osteoma of the Internal Auditory Canal

Abstract: The lack of a consistent presentation despite a similar radiographic appearance suggests that the osteoma is often an incidental finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 14 publications
0
25
0
1
Order By: Relevance
“…Cranial vault lesions would be better compared to lesions of the external auditory canal. Thawley et al (1999) and Vrabec et al (2000) differentiated auditory canal lesions into osteomas and exostoses. An osteoma is defined as an isolated bony, exophytic, pedunculated papillomatous protrusion with a narrow neck.…”
Section: Is Btl An Osteoma?mentioning
confidence: 99%
“…Cranial vault lesions would be better compared to lesions of the external auditory canal. Thawley et al (1999) and Vrabec et al (2000) differentiated auditory canal lesions into osteomas and exostoses. An osteoma is defined as an isolated bony, exophytic, pedunculated papillomatous protrusion with a narrow neck.…”
Section: Is Btl An Osteoma?mentioning
confidence: 99%
“…A previous review of 13 cases of IAC osteoma reported from 1882 to 1993 identified several clinical characteristics as follows: mean age of 57 years; female-to-male ratio of 5.5:1, suggesting a particular predilection for postmenopausal women; and 42% of the patients had no symptoms, 42% had hearing loss, 25% had tinnitus, and 33% had vertigo (Clerico et al 1994). Our present study summarized and reviewed 17 cases of IAC osteoma reported in the past 22 years (1992-2013) (Singh et al 1992;Ramsay and Brackmann 1994;Coakley et al 1996;Wright et al 1996;Boedts et al 1997;Davis et al 2000;Vrabec et al 2000;Kovacić et al 2001;Gerganov et al 2008;Liétin et al 2010;Baik et al 2011;Kaymakci et al 2012;Plantone et al 2013) and excluded the previously reviewed cases by Clerico et al (1994) (Table 1). Mean age was 44.1 years (male: 44.0, female: 44.2), and femaleto-male ratio was 1.4:1.…”
Section: Discussionmentioning
confidence: 99%
“…Further improvements in imaging technology are needed for effective neuroimaging diagnosis of small IAC tumors. The differential diagnoses of IAC osteoma with the exception of bony lesions include vestibular schwannoma, facial nerve schwannoma, meningioma, hemangioma, lipoma, and cholesteatoma (Vrabec et al 2000). With the widespread introduction of imaging devices, the incidental diagnosis of smaller and asymptomatic vestibular schwannomas has increased (Lin et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to primary causes of IAC narrowing, an osseous lesion such as an exostosis or an osteoma can cause secondary narrowing of IAC. Also Paget's disease, otosclerosis and fibrous dysplasia can cause narrowing of the canal [6][7][8] .…”
Section: Discussionmentioning
confidence: 99%